Industrial training report: Perpustakaan Tun Abdul Razak, UiTM Cawangan Selangor Kampus Puncak Alam / Nur Elisya Ismikhairul - Ismikhairul, Nur Elisya (Faculty of Information Management, 2022)
Industrial training is one of the requirements for the final year student to finish their studies and must be properly complete to qualify the student road to the graduation day. PTAR Kampus Puncak Alam (PTARKPA) was my choice to undergo five months of my Industrial Training starting from 7 March to 5 August 2022. During five months period of industrial training, I was supervised by Mrs. Norhafiza Mustape as a Senior Librarian. I have been assigned to accomplished various tasks which included administrative works, preparing online database talk and library management day-today activities regarding to instruction given by my supervisor and the staffs there. Not only that, during industrial also, me as student implemented a special project requested by lecturer and librarian at PTARKPA. Special project is one of the parts that is important for the practical student to improve or propose something useful and significant for the organization where they are working during internship or industrial training. Throughout my industrial training, I was able to apply the skill and knowledge acquired from lecturer to complete my work in practices. Besides that, I learn many skills and get more experienced during my internship at PTARKPA.